Multifunctional Equipment for Low-temperature Separation of Food Solutions Based on The Effect of “Thermal Paradox” - Burdo O.G.; Terziev S. G.; Mordynskiy V.P.; Sirotyuk I.V.; Fateeva Ya.A. (Problems of the Regional Energetics)
The analysis of studies devoted to food solutions separation was carried out. The evolution of cryoconcentration technologies is analyzed, including the research works of the authors in the field of the block freezing plants. The purpose of the work is to reduce energy costs in block freezing plants and to intensify the process of the ice block formation. A hypothesis states that energy efficiency can be improved by recycling ice, using its energy to supercool the refrigerant before throttling. To intensify heat and mass transfer during crystallization, a scientific and technical idea for the implementation of the "thermal paradox effect" is proposed. The essence of the effect is that, with a certain combination of design and operating parameters of a block freezer, the growth of an ice block leads to a decrease in the total thermal resistance in the circuit "refrigerant — block freezer's wall — ice block — solution". The most significant result of the work was that it proved the possibility to harmonize the design and operating parameters and organized the process of separation the solutions into ice and concentrate while minimizing systemic cold losses, and, and thus the ways were proposed for developing the freezing concentration technique. The scientific significance of the obtained results lies in the fact that a new prin-ciple of efficient use of the ice block energy was proved in the work, and a new effect was obtained, which it was referred to by the authors as the "thermal paradox". The practical significance of the work was that a multifunctional freezing unit with ice recycling and frequency con-trol of the compressor drive was created.